Dual polarization measurements of MWA beampatterns at 137 MHz. Issue 2 (20th January 2021) - Chokshi, A; Line, J L B; Barry, N; Ung, D; Kenney, D; McPhail, A; Williams, A; Webster, R L
ABSTRACT: The wide adoption of low-frequency radio interferometers as a tool for deeper and higher resolution astronomical observations has revolutionized radio astronomy. Despite their construction from static, relatively simple dipoles, the sheer number of distinct elements introduces new, complicated instrumental effects. Their necessary remote locations exacerbate failure rates, while electronic interactions between the many adjacent receiving elements can lead to non-trivial instrumental effects. The Murchison Widefield Array (MWA) employs phased array antenna elements (tiles), which improve collecting area at the expense of complex beam shapes. Advanced electromagnetic simulations have produced the fully embedded element (FEE) simulated beam model which has been highly successful in describing the ideal beam response of MWA antennas. This work focuses on the relatively unexplored aspect of various in-situ, environmental perturbations to beam models and represents the first large-scale, in-situ, all-sky measurement of MWA beam shapes at multiple polarizations and pointings. Our satellite based beam measurement approach enables all-sky beam response measurements with a dynamic range of ∼50 dB, at 137 MHz.